Insurance spares, safety equipment and spare parts on ships - Kotze, Johan L (Department of Commercial Law, 2023)
This paper deals with the treatment of spare parts on ships, in accordance with the Income Tax Act, No. 58 of 1962 (as amended), (hereafter 'the Act'). The question that is central to this issue is specifically when a spare part is brought into use. Flowing from this is the question of the purpose of a spare part. In summary the issues are as follow: What expenditure should properly be regarded as forming part of the cost of a ship? The expenditure envisaged here comprises essential safety equipment and spares included in a ship at the time of its construction prior to commissioning and its maiden voyage. If such expenditure is considered not to form part of the cost of a ship, should it in the alternative be deducted as operating expenditure? Should it then be included in trading stock as 'consumable stores and spare parts ... used or consumed' by virtue of having been brought into use or consumed when added to the ship? Should the cost of the subsequent replacement of the above items properly be regarded as operating expenditure? Apparently an airline received a written ruling from the Commissioner for the South African Revenue Services that if an aircraft is acquired with a spare engine, it will be regarded as part and parcel of the plane. It will be regarded as one asset for taxation purposes on which wear and tear is permitted. The airline is not required to include this 'spare' engine as a spare part for trading stock purposes.